If headache has any association with hypertension, it is negative. Evidence from a population-based study in Nepal. (November 2021) - Manandhar, Kedar; Risal, Ajay; Koju, Rajendra; Linde, Mattias; Steiner, Timothy J
Background: Hypertension and headache disorders are major contributors to public ill health, linked by a long-standing but questionable belief that hypertension is a conspicuous cause of headache. In Nepal, where hypertension is common and often untreated, we assessed the substance of this belief, hypothesising that, should hypertension be a significant cause of headache, a clear positive association between these disorders would exist. Methods: In a cross-sectional, nationwide study, trained health workers conducted face-to-face structured interviews, during unannounced home visits, with a representative sample of the Nepalese adult population (18–65 years). They applied standard diagnostic criteria for headache disorders and measured blood pressure digitally. Hypertension was defined as systolic pressure ≥140 and/or diastolic ≥90 mm Hg. Results: Of 2, 100 participants (59.0% female, mean age 36.4 ± 12.8 years), 317 (15.1%) had hypertension (41.0% female) and 1, 794 (85.4%) had headache (61.6% female; 728 migraine, 863 tension-type headache, 161 headache on ≥15 days/month [mutually exclusive diagnoses]; 42 unclassified headaches). All headache collectively was less prevalent among hypertension cases (78.9%) than non-cases (86.6%; p = 0.001). A negative association between hypertension and all headache was demonstrated in bivariate analysis (odds ratio: 0.6 [95% Confidence interval: 0.4–0.8]; p < 0.001), but did not maintain significance in multivariate regression analysis (adjusted odds ratio: 0.8 [95% Confidence interval: 0.5–1.1]; p = 0.09). The findings were reflected, without significance, in each headache type. Conclusions: If any association exists between hypertension and headache disorders, it is negative. From the public-health perspective, headache disorders and hypertension are unrelated entities: they need distinct policies and programs for prevention, control and management.